Physiological Changes in Mesembryanthemum crystallinum During the C3 to CAM Transition Induced by Salt Stress - Guan, Qijie; Tan, Bowen; Kelley, Theresa M.; Tian, Jingkui; Chen, Sixue (Frontiers in Plant Science, 2020)
Salt stress impedes plant growth and development, and leads to yield loss. Recently, a halophyte species Mesembryanthemum crystallinum has become a model to study plant photosynthetic responses to salt stress. It has an adaptive mechanism of shifting from C3 photosynthesis to crassulacean acid metabolism (CAM) photosynthesis under stresses, which greatly enhances water usage efficiency and stress tolerance. In this study, we focused on investigating the morphological and physiological changes [e.g., leaf area, stomatal movement behavior, gas exchange, leaf succulence, and relative water content (RWC)] of M. crystallinum during the C3 to CAM photosynthetic transition under salt stress. Our results showed that in M. crystallinum seedlings, CAM photosynthesis was initiated after 6 days of salt treatment, the transition takes place within a 3-day period, and plants became mostly CAM in 2 weeks. This result defined the transition period of a facultative CAM plant, laid a foundation for future studies on identifying the molecular switches responsible for the transition from C3 to CAM, and contributed to the ultimate goal of engineering CAM characteristics into C3 crops.